2011
DOI: 10.1001/archpediatrics.2010.287
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Outcomes of Children Growing Up With Chronic Illness

Abstract: To examine young adult outcomes in a nationally representative US cohort of young adults growing up with a chronic illness. Design: Secondary analysis of nationally representative data from wave III (in 2001) of the National Longitudinal Study of Adolescent Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…These findings corroborate past research on children/adolescents with chronic conditions, 4,11 indicating that young adults with diabetes have similar negative psychosocial outcomes to children with chronic conditions. Findings from the current study extend past research on young adults with chronic conditions, 5,8 in that several health behaviors and psychosocial variables were measured rather than focusing solely on socio-economic variables. This study confirms that young adults with chronic conditions seem to experience similar social successes such as having a significant other, having children, and education endeavors as compared to young adults without chronic conditions, 5,8 but extends the literature by showing strong positive associations between having diabetes and several negative health behaviors and psychosocial outcomes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These findings corroborate past research on children/adolescents with chronic conditions, 4,11 indicating that young adults with diabetes have similar negative psychosocial outcomes to children with chronic conditions. Findings from the current study extend past research on young adults with chronic conditions, 5,8 in that several health behaviors and psychosocial variables were measured rather than focusing solely on socio-economic variables. This study confirms that young adults with chronic conditions seem to experience similar social successes such as having a significant other, having children, and education endeavors as compared to young adults without chronic conditions, 5,8 but extends the literature by showing strong positive associations between having diabetes and several negative health behaviors and psychosocial outcomes.…”
Section: Discussionsupporting
confidence: 68%
“…The few studies that have looked at health behaviors and psychosocial outcomes among young adults with chronic health conditions have shown that while young adults with chronic conditions were equally as likely to be married and have children compared to young adults without chronic conditions, they were more likely to be of lower socio-economic status (SES) and receive public assistance, and less likely to graduate from high school or be employed. 5,8 As these studies have focused primarily on socio-demographic differences, additional research is needed to understand whether young adults with chronic conditions are differentially likely to experience other negative outcomes such as higher BMI, less healthful behaviors (e.g. unhealthy dietary intake, less physical activity), more psychological problems, and increased social stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have investigated educational attainment for YCMC and found similar gaps in attainment, 17,20,2326 although few studies have been able to assess the extent to which these disparities stem from underlying differences in educational aspirations or expectations, or pinpoint where in the educational trajectory YCMC are most likely to fall behind their peers. We identified that even prior to completing high school, YCMC and their parents report lower expectations for attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Some research suggests that students with diabetes have relatively lower completion rates as compared to peers and achieve slightly lower final grades, particularly if diagnosed at a very early age [2224]. A recent study using data from the National Longitudinal Study of Adolescent Health found that young adults with diabetes were 6% more likely to drop out of high school and, after controlling for related factors, completed .25 fewer years of schooling than healthy peers; however, the authors did not distinguish between type 1 or type 2 diabetes [25].…”
Section: Young Adulthood and Lifestyle Considerationsmentioning
confidence: 99%